Studi Lafaz Din, Millah, Ummah dan Huda dalam Al-Qur’an - Furqan Furqan; Khairatur Ridhatillah (TAFSE: Journal of Qur'anic Studies, 2022)
One of the specialties of the Qur'an is that it is rich in vocabulary. As there are two or more lafazes used to denote one meaning or meaning adjacent. Al-din, millah, ummah and huda are synonymous lafaz, the words mean religion, but the Qur'an uses them in different connotations. This research is a literature study with a maudhui method approach and content analysis techniques (content analysis). The results showed that lafaz al-din is mentioned 92 times in the Qur'an which is contained in 82 verses. According to Quraish Shihab, lafaz al-din means submission, obedience, calculation, religion and recompense. Ibn Katsir interpreted lafaz al-din as the meaning of obedience. Lafaz millah is mentioned 14 times in the Qur'an. According to Quraish Shihab, this lafaz means a set of teachings and according to Ibn Katsir it means religion (i.e. Islam) brought by prophet Ibrahim. Lafaz ummah with its various forms is found as many as 64 words with varying meanings. In the singular it is called 51 times and the plural form 13 times. According to Ibn Katsir, lafaz ummah means religion and tawhid. Lafaz huda in the Qur'an is mentioned in six forms with 73 derivations, each form has its own meaning. According to al-Maraghi, lafaz huda means religion and instruction, while Quraish Shihab argues that lafaz huda means divine hidayah, the teachings brought by the Prophet Muhammad, hidayah, taufik and Islamic teachings. Salah satu keistimewaan Alquran adalah kaya akan kosakata. Seperti terdapat dua lafaz atau lebih yang digunakan untuk menunjukkan satu makna atau makna yang berdekatan. Al-din, millah, ummah dan huda merupakan lafaz sinonim, kata-kata tersebut berarti agama, tetapi Alquran memakainya dalam konotasi yang berbeda. Penelitian ini adalah studi kepustakaan dengan pendekatan metode maudhui dan teknik analisis isi (content analisys). Hasil penelitian menunjukkan bahwa lafaz al-din disebutkan sebanyak 92 kali dalam Alquran yang terdapat pada 82 ayat. Menurut Quraish Shihab, lafaz al-din bermakna ketundukan, ketaatan, perhitungan, agama dan balasan. Ibnu Katsir menafsirkan lafaz al-din bermakna ketaatan. Lafaz millah disebutkan 14 kali dalam Alquran. Menurut Quraish Shihab, lafaz ini bermakna sekumpulan ajaran dan menurut Ibnu Katsir bermakna agama (yaitu Islam) yang dibawa oleh Nabi Ibrahim. Lafaz ummah dengan berbagai bentuknya dijumpai sebanyak 64 kata dengan arti yang bervariasi. Dalam bentuk tunggal disebut sebanyak 51 kali dan bentuk jamak 13 kali. Menurut Ibnu Katsir, lafaz ummah bermakna agama dan tauhid. Lafaz huda dalam Alquran disebutkan dalam enam bentuk dengan 73 derivasi, setiap bentuk memiliki arti tersendiri. Menurut al-Maraghi, lafaz huda bermakna agama dan petunjuk, sedangkan Quraish Shihab berpendapat lafaz huda bermakna hidayah ilahi, ajaran yang dibawa oleh Nabi Muhammad, hidayah, taufik dan ajaran Islam.